Honeysuckle flowers extract loaded Bombyx mori silk fibroin films for inducing apoptosis of HeLa cells - Li, Chenlin (Microsc Res Tech, 2017)
This study aimed to prepare silk fibroin (SF) films loaded with honeysuckle flowers extract (HFE) for inducing apoptosis of HeLa cells. We mixed solution of SF and HFE by air‐drying for preparing the honeysuckle flowers extract loaded silk fibroin (SFH) films. The physical properties including morphologies, contact angle, roughness, and Z range were characterized. MTS assay and fluorescence micrographs proved that SFH films inhibited the proliferation rate of HeLa cells due to induction of HFE into SF films. Furthermore, cell apoptosis assay and cell cycle analysis confirmed that the apoptosis of HeLa cells resulted from SFH films. Therefore, SFH films designed in our study might be a promising candidate material for cancer therapy.